Time-Course Evaluation of Body Mass Index in Japanese Children With Obstructive Sleep Apnea Syndrome After Adenotonsillectomy: A Three-Years Follow-Up Study - Fukuda, Ken; Yasudo, Hiroki; Ohta, Naoki; Narumi, Hiroko; Abe, Nozomi; Tarumoto, Shunsuke; Yamashita, Hiroshi; Ichihara, Kiyoshi; Ohga, Shouichi; Hasegawa, Shunji (Frontiers in Pediatrics, 2020)
Delayed physical growth is a common complication of paediatric obstructive sleep apnoea syndrome (OSAS). Adenotonsillectomy (AT) is the first-line treatment for paediatric OSAS. Only a few studies have performed time-course BMI evaluation in paediatric OSAS patients postoperatively. Thus, we aimed to evaluate the time-course changes in paediatric OSAS patients after AT. Thirty-three children with OSAS who underwent AT were included and were divided into two groups on the basis of the BMI z-score (delayed physical growth group, n=15; non-delayed physical growth group, n=18). The clinical records of height and weight were collected before AT and at 6, 12, 24, and 36 months after AT. The changes in the mean BMI z-scores of the two groups were assessed up to 36 months. The mean BMI z-score was significantly increased in the delayed physical growth group at 6 months after AT. In contrast, the increase in mean BMI z-score was not observed in the non-delayed physical growth group. Growth improvement was noted in the paediatric OSAS patients with delayed physical growth after AT. Our results suggest that AT is a promising therapy for improving physical growth of paediatric OSAS patients with such problems.